Bio-based foam adsorption material as well as preparation method and adsorption application thereof

By using bio-based polymers and adsorbents and other materials to prepare high-porosity foams, combined with hydrophobic modification, the problems of insufficient adsorption capacity and difficulty in recycling of traditional foam materials are solved, and efficient adsorption and separation of organic pollutants in water are achieved. Advantages of environmental protection and biodegradation.

CN119488883AInactive Publication Date: 2025-02-21UNIV OF SCI & TECH OF CHINA

Patent Information

Application Number
CN202510076409.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-02-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When treating oil-containing wastewater, the separation efficiency is low, the material is difficult to recycle, secondary pollution and environmental impact are present, and the adsorption capacity of traditional foam materials is insufficient, difficult to recycle, and difficult to degrade, resulting in environmental pollution.

Method used

Using bio-based polymers as foam skeleton, combining adsorbents, crosslinking agents and reinforcers with large specific surface area to form foam materials with high porosity and high adsorption capacity, and modifying hydrophobic agents to achieve oil in wastewater and efficient adsorption and separation of organic dyes.

Benefits of technology

It has achieved efficient adsorption and separation of organic pollutants in water, and the materials can be recycled, which is biodegradable and environmentally friendly, reducing the risk of secondary pollution to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488883A_ABST
    Figure CN119488883A_ABST
Patent Text Reader

Abstract

The invention discloses a bio-based foam adsorption material as well as a preparation method and adsorption application thereof. The bio-based polymer is used as a foam skeleton, the adsorbent with a large specific surface area is added to further improve the foam adsorption capacity, the cross-linking agent and the reinforcing filler improve the overall strength of the foam, and the bio-based foam adsorption material with the high adsorption capacity is obtained. The bio-based foam disclosed by the invention is light in weight, controllable in hydrophilicity and hydrophobicity, and capable of separating and removing pollutants such as oil and organic dye. The foam has high adsorption capacity and good cyclic adsorption capacity, can be repeatedly used, is biodegradable, does not pollute the environment, can effectively adsorb dangerous chemicals existing in a water body, does not cause secondary pollution, and can be used for decontamination treatment of organic pollutants in industrial wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer materials, and specifically relates to a bio-based foam adsorption material and a preparation method and adsorption application thereof. Background Art

[0002] While industrial development brings convenience to our lives, it also brings serious harm to the environment. Water pollution has intensified. Most of the organic pollutants contained in it are toxic and non-biodegradable. The wanton discharge will harm animals and plants, and will also threaten human health through bioaccumulation. Therefore, it is urgent to take measures to control the pollution caused by oily wastewater. At present, there are many methods to solve the pollution of oily wastewater, including gravity separation, mechanical recovery, centrifugation, in-situ combustion, chemical solidification, electrolysis and bioremediation. However, these methods still have limitations such as low separation efficiency, secondary pollution, high energy consumption and high cost, which greatly restricts their actual large-scale application. These methods usually produce limited oil / water separation performance, and the separation effect does not meet the requirements of reuse. In addition, the materials used in this process, such as super-hydrophobic stainless steel mesh, TiO2 nanowire membrane, etc., are often not recyclable and are not environmentally friendly.

[0003] Among the methods for treating organic oils, adsorption separation and gravity separation are considered to be one of the most effective technologies for removing oily pollutants from water. Materials with superwetting properties can be modified to have relatively good oil / water separation performance. The technology of using melamine foam or polyurethane soft foam to absorb oil has been reported. Although it has a good adsorption effect, it also has the problem that the pore structure of traditional foams is large, the adsorption area is not high enough, the foam is difficult to reuse after adsorption, and it is not easy to degrade and easily causes secondary pollution to the environment. According to literature reports, the team of Zhu Jin, a researcher at the Ningbo Institute of Materials Technology and Engineering, Chinese Academy of Sciences, used lignin foaming to prepare polyurethane foam, which can achieve crude oil cleaning. The modified foam can adsorb more than 6.34 times its weight of crude oil within 6 minutes, and can also be degraded in alkaline solutions (Chemical Engineering Journal 2021, 415, 128956). Foam materials prepared from bio-based polymers such as cyclodextrin have also been used to adsorb organic micropollutants such as bisphenol A, and the separation and removal rate of crude oil pollutants can reach 95% (Nature 2016, 529, 190-194). However, the synthesis of polyurethane foam from biomass raw materials for oil absorption still requires isocyanate for foaming, has large pores and low adsorption rate, and can only be degraded in alkaline solution. The degradation rate is very slow under normal environmental conditions. The maximum oil absorption of polyurethane oil-absorbing foam modified with acetylated lignin is only 8.94 g / g (CN 114957969 A). Therefore, the development of new bio-based polymer foam materials can solve the problem of biodegradation, but the adsorption rate of foam materials for organic solvents is rarely reported. Therefore, it is necessary to develop a biodegradable and environmentally friendly biomass oil-water separation foam material that can efficiently adsorb organic pollutants in water and can be recycled. Summary of the invention

[0004] The present invention aims to provide a bio-based foam adsorption material in view of the shortcomings and deficiencies of traditional foam adsorption materials. The foam material is mainly used for the adsorption and separation of organic hazardous chemical pollutants in industry. It has rich pore structure, low mass density, high adsorption performance, large specific surface area, and is green and non-toxic, biocompatible and biodegradable. It conforms to the scientific concept of green chemistry and can effectively solve the problems of insufficient adsorption capacity of traditional modified foams, difficulty in recycling, and difficulty in reducing secondary pollution to the environment.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is: The bio-based foam adsorption material of the present invention uses a bio-based polymer as a foam skeleton, adds an adsorbent with a large specific surface area to improve the foam adsorption capacity, and uses a cross-linking agent and a reinforcing filler to improve the overall strength of the foam. Finally, it is modified with a hydrophobic agent to adjust the hydrophilicity and hydrophobicity, and can adsorb oils and organic dyes in wastewater, and can be recycled after use.

[0006] The bio-based foam adsorption material of the present invention is obtained by processing raw materials including the following mass fractions: 0.1~10 parts of bio-based polymer, 0.01~5 parts of adsorbent, 0.1~10 parts of cross-linking agent, 0.01~5 parts of reinforcing agent, and 0.01~5 parts of hydrophobic modifier.

[0007] The bio-based polymer is a combination of one or more of carrageenan, sodium alginate, carboxymethyl cellulose, gelatin, cellulose nanofiber, konjac glucomannan, hydroxyethyl cellulose, chitosan, gum arabic, gellan gum, and starch.

[0008] The adsorbent is a combination of one or more of vermiculite, sepiolite, montmorillonite, layered double hydroxide, zeolite, metal-organic framework material, and halloysite nanotube.

[0009] The cross-linking agent is a combination of one or more of glutaraldehyde, formaldehyde, genipin, polyvinyl alcohol, ferric chloride, aluminum chloride, and polyamide-epichlorohydrin.

[0010] The reinforcing agent is a combination of one or more of glass fiber, silica fiber, attapulgite, mullite fiber, zirconium dioxide fiber and carbon fiber.

[0011] The hydrophobic modifier is any one or more combinations of methyltrimethoxysilane, hexadecyltriethoxysilane, 1H,1H,2H,2H-perfluorodecyltrichlorosilane, and polydimethylsiloxane.

[0012] The method for preparing the bio-based foam adsorption material of the present invention comprises the following steps: The bio-based polymer, adsorbent, enhancer and water are stirred and mixed at 500-5000 r / min for 30 s-10 h at 0-90°C to obtain a first mixed solution; the cross-linking agent is added to the first mixed solution at 0-90°C and stirred and mixed at 100-10000 r / min for 30 s-30 min to obtain a second mixed solution; the second mixed solution is poured into a mold for molding and drying to obtain a bio-based foam; a hydrophobic modifier is added to the bio-based foam for hydrophobic modification to obtain a bio-based foam adsorption material.

[0013] In the first mixed solution, the mass fraction of the bio-based polymer in water is 0.1% to 10%; the mass fraction of the adsorbent in water is 0.01% to 5%; and the mass fraction of the enhancer in water is 0.01% to 5%.

[0014] In the second mixed solution, the mass fraction of the cross-linking agent is 0.1% to 10%.

[0015] The drying method of the second mixed liquid includes one or more combinations of freeze drying, drying at room temperature and pressure, heating drying, and supercritical CO2 drying.

[0016] The hydrophobic modification method comprises soaking the bio-based foam in a hydrophobic modifier solution, vapor-phase evaporation deposition of the hydrophobic modifier, and spraying of the hydrophobic modifier, or one or more combinations thereof.

[0017] The bio-based foam adsorption material of the present invention is used in adsorbing and separating organic pollutants in water.

[0018] The organic pollutants include oils, organic dyes, etc. For example, petroleum ether, ethylene dichloride, methylene chloride, chloroform, methyl red, toluene, carbon tetrachloride, etc.

[0019] The present invention relates to a bio-based foam adsorption material, the main components of which are a bio-based polymer, an adsorbent, a cross-linking agent, a reinforcing agent, and a hydrophobic modifier. The above-mentioned bio-based polymer and the cross-linking agent can be cross-linked to form a three-dimensional foam skeleton network, and the reinforcing agent and the adsorbent can enhance the strength of the foam skeleton, and at the same time can increase the porosity and improve the adsorption capacity. When treating aqueous solutions of hazardous chemicals, the organic solvent can be separated and processed by gravity filtration separation. The foam adsorption material can be suspended on the surface of wastewater to automatically adsorb organic pollutants to achieve wastewater purification, and can also be connected to a water pump to achieve continuous separation of oil and water pollutants.

[0020] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) Compared with traditional modified foams, its raw materials are bio-based polymers, which can be naturally degraded in the environment and have no impact on the environment.

[0021] (2) The foam uses bio-based polymers to form the foam skeleton and combines with adsorbents to have higher porosity and organic pollutant adsorption capacity.

[0022] (3) In addition to the bio-based polymer, the foam also contains a reinforcing agent, which enhances the skeleton strength of the bio-based foam and extends the recycling time of the foam.

[0023] (4) The foam raw materials are easy to obtain, the foam preparation method is simple, and it can be prepared on a large scale, which has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 This is a contact angle test photograph of Example 1.

[0026] Figure 2 This is a contact angle test photograph of Comparative Example 1.

[0027] Figure 3 is a SEM image of the bio-based adsorption foam of Example 1.

[0028] Figure 4 This is the SEM image of the bio-based adsorption foam of Comparative Example 1.

[0029] Figure 5 This is the efficiency diagram of Example 3 after the first and tenth cycle separation of mixed solutions of different types of organic hazardous chemical solvents and water.

[0030] Figure 6 This is the efficiency diagram of Example 3 after the first and tenth cycle separation of mixed solutions of different types of organic hazardous chemical solvents and water.

[0031] Figure 7 This is a curve diagram of the removal efficiency and adsorption capacity of a mixed solution of petroleum ether and water in Example 3 as a function of the number of adsorption cycles.

[0032] Figure 8 This is a curve diagram of the removal efficiency and adsorption capacity of a mixed solution of petroleum ether and water in comparative example 3 as a function of the number of adsorption cycles.

[0033] Fig. 9 This is the curve of the degradation rate of the bio-based foam adsorbent material in Example 2 over time (tested 5 times in parallel). DETAILED DESCRIPTION

[0034] In order to further illustrate the technical solution of the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention. Based on the examples in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0035] The present invention is further described in detail below with reference to examples, but the embodiments of the present invention are not limited thereto.

[0036] Embodiment 1:

[0037] 1.5 g of carrageenan powder, 1.5 g of vermiculite powder, and 0.25 g of silica fiber were weighed and dissolved in 100 g of deionized water, and stirred at 3000 r / min for at least 2 h at 60 ° C to completely dissolve them to obtain a first mixed solution; then 0.5 g of ferric chloride was added to the first mixed solution at 60 ° C and stirred at 3000 r / min for 5 min to obtain a second mixed solution; the second mixed solution was poured into a mold and placed in a refrigerator for freezing and forming, and then freeze-dried to obtain a bio-based foam; the bio-based foam was immersed in an ethanol solution of polydimethylsiloxane for 3 min for hydrophobic modification, and the bio-based foam adsorption material was obtained after drying.

[0038] Embodiment 2:

[0039] 1.5 g of carrageenan powder, 1.5 g of montmorillonite powder, and 0.25 g of silica fiber were weighed and dissolved in 100 g of deionized water, and stirred at 3000 r / min for at least 2 h at 60 ° C to completely dissolve them to obtain a first mixed solution; then 0.5 g of ferric chloride was added to the first mixed solution at 60 ° C and stirred at 3000 r / min for 5 min to obtain a second mixed solution; the second mixed solution was poured into a mold and placed in a refrigerator for freezing molding, and then freeze-dried to obtain a bio-based foam; the bio-based foam was immersed in an ethanol solution of polydimethylsiloxane for 5 min for hydrophobic modification, and the bio-based foam adsorption material was obtained after drying.

[0040] Embodiment 3:

[0041] 2.0 g of cellulose nanofiber powder, 1.5 g of halloysite powder, and 0.25 g of glass fiber were weighed and dissolved in 100 g of deionized water, and stirred at 50°C and 5000 r / min for at least 2 h to completely dissolve them to obtain a first mixed solution; then 0.5 g of polyamide-epichlorohydrin was added to the first mixed solution at 20°C and stirred at 3000 r / min for 5 min to obtain a second mixed solution; the second mixed solution was poured into a mold and placed in a refrigerator for freezing molding, and then freeze-dried to obtain a bio-based foam; the bio-based foam was immersed in an ethanol solution of methyltrimethoxysilane for 3 min for hydrophobic modification, and the bio-based foam adsorption material was obtained after drying.

[0042] The hydrophobic modified bio-based foam adsorption material is placed in an oil-containing aqueous solution to adsorb the oil in the water. The adsorbed liquid is squeezed out of the foam material that adsorbs the oil, and then it can be placed in an oil-water mixture again to adsorb pollutants. The above hydrophobic / oleophilic bio-based foam is used to adsorb light oil (petroleum ether) on water and heavy oil (dichloromethane) underwater. The oil is quickly absorbed by the foam, realizing the separation of the oil-water mixture and the recovery of oil. The weight of the foam before absorbing the oil is recorded as m1, and the weight of the foam after absorbing the oil is recorded as m2. The saturated oil absorption capacity k of the foam is calculated according to the formula, k=(m2-m1) / m1. The organic pollutants are replaced with dichloroethane, chloroform, methyl red, toluene, carbon tetrachloride, etc., and the adsorption capacity of different organic matter is tested.

[0043] The degradation rate of the prepared bio-based foam adsorbent material was tested. First, the dry sample was accurately weighed (accurate to 0.001 g) and buried in a jar containing commercial soil, 5 cm deep from the surface. The sample was stored at room temperature for 30 days. Tap water was added regularly during the experiment to offset the drying caused by soil evaporation. The weight of the sample was collected every 5 days, then washed with water and dried at 45°C for 24 hours. The difference in sample weight loss indicates the degree of degradation. The degree of degradation (D) is calculated by the following formula:

[0044] Among them, W i is the initial weight of the sample before degradation, W f It refers to the weight after a specific time interval of biodegradation.

[0045] Embodiment 4:

[0046] 1.0 g of cellulose nanofiber powder, 1.5 g of halloysite powder, and 0.25 g of glass fiber were weighed and dissolved in 100 g of deionized water, and stirred at 50°C and 5000 r / min for at least 2 h to completely dissolve them to obtain a first mixed solution; then 0.5 g of polyamide-epichlorohydrin was added to the first mixed solution at 20°C and stirred at 3000 r / min for 5 min to obtain a second mixed solution; the second mixed solution was poured into a mold and placed in a refrigerator for freezing molding, and then freeze-dried to obtain a bio-based foam; the bio-based foam was immersed in an ethanol solution of methyltrimethoxysilane for 3 min for hydrophobic modification, and the bio-based foam adsorption material was obtained after drying.

[0047] Embodiment 5:

[0048] 2.0 g of chitosan powder, 0.5 g of halloysite powder and 0.25 g of glass fiber were weighed and dissolved in 100 g of deionized water, and stirred at 50° C. and 5000 r / min for at least 2 h to completely dissolve them to obtain a first mixed solution; then 0.5 g of polyamide-epichlorohydrin was added to the first mixed solution at 20° C. and stirred at 3000 r / min for 5 min to obtain a second mixed solution; the second mixed solution was poured into a mold and placed in a refrigerator for freezing molding, and then freeze-dried to obtain a bio-based foam; the bio-based foam was immersed in an ethanol solution of methyltrimethoxysilane for 3 min for hydrophobic modification, and the bio-based foam adsorption material was obtained after drying.

[0049] Embodiment 6:

[0050] 2.0 g of cellulose nanofiber powder, 0.5 g of halloysite powder, and 0.25 g of glass fiber were weighed and dissolved in 100 g of deionized water, and stirred at 50°C and 5000 r / min for at least 2 h to completely dissolve them to obtain a first mixed solution; then 0.5 g of polyamide-epichlorohydrin was added to the first mixed solution at 20°C and stirred at 3000 r / min for 5 min to obtain a second mixed solution; the second mixed solution was poured into a mold and placed in a refrigerator for freezing molding, and then freeze-dried to obtain a bio-based foam; the bio-based foam was immersed in an ethanol solution of methyltrimethoxysilane for 3 min for hydrophobic modification, and the bio-based foam adsorption material was obtained after drying.

[0051] Embodiment 7:

[0052] 2.0 g of carrageenan powder, 1.5 g of vermiculite powder, and 0.25 g of silica fiber were weighed and dissolved in 100 g of deionized water, and stirred at 3000 r / min for at least 2 h at 60 ° C to completely dissolve them to obtain a first mixed solution; then 0.5 g of ferric chloride was added to the first mixed solution at 60 ° C and stirred at 3000 r / min for 5 min to obtain a second mixed solution; the second mixed solution was poured into a mold and placed in a refrigerator for freezing and forming, and then freeze-dried to obtain a bio-based foam; the bio-based foam was immersed in an ethanol solution of polydimethylsiloxane for 3 min for hydrophobic modification, and the bio-based foam adsorption material was obtained after drying.

[0053] Embodiment 8:

[0054] 2.0 g of carrageenan powder, 1.5 g of vermiculite powder, and 0.25 g of carbon fiber were weighed and dissolved in 100 g of deionized water, and stirred at 3000 r / min for at least 2 h at 60 ° C to completely dissolve them to obtain a first mixed solution; then 0.5 g of ferric chloride was added to the first mixed solution at 60 ° C and stirred at 3000 r / min for 5 min to obtain a second mixed solution; the second mixed solution was poured into a mold and placed in a refrigerator for freezing and forming, and then freeze-dried to obtain a bio-based foam; the bio-based foam was immersed in an ethanol solution of polydimethylsiloxane for 3 min for hydrophobic modification, and the bio-based foam adsorption material was obtained after drying.

[0055] Embodiment 9:

[0056] 1.0 g of cellulose nanofiber powder, 1.5 g of halloysite powder, and 0.25 g of glass fiber were weighed and dissolved in 100 g of deionized water, and stirred at 50°C and 5000 r / min for at least 2 h to completely dissolve them to obtain a first mixed solution; then 0.5 g of polyamide-epichlorohydrin was added to the first mixed solution at 20°C and stirred at 3000 r / min for 5 min to obtain a second mixed solution; the second mixed solution was poured into a mold and placed in a refrigerator for freezing molding, and then freeze-dried to obtain a bio-based foam; the bio-based foam was immersed in an ethanol solution of methyltrimethoxysilane for 3 min for hydrophobic modification, and the bio-based foam adsorption material was obtained after drying.

[0057] Embodiment 10:

[0058] 1.0 g of cellulose nanofiber powder, 1.5 g of halloysite powder, and 0.25 g of glass fiber were weighed and dissolved in 100 g of deionized water, and stirred at 50°C and 5000 r / min for at least 2 h to completely dissolve them to obtain a first mixed solution; then 0.5 g of polyamide-epichlorohydrin was added to the first mixed solution at 20°C and stirred at 8000 r / min for 5 min to obtain a second mixed solution; the second mixed solution was poured into a mold and placed in a refrigerator for freezing molding, and then freeze-dried to obtain a bio-based foam; the bio-based foam was immersed in an ethanol solution of methyltrimethoxysilane for 3 min for hydrophobic modification, and the bio-based foam adsorption material was obtained after drying.

[0059] Embodiment 11:

[0060] 1.0 g of cellulose nanofiber powder, 1.5 g of halloysite powder, and 0.25 g of glass fiber were weighed and dissolved in 100 g of deionized water, and stirred at 50°C and 5000 r / min for at least 2 h to completely dissolve them to obtain a mixed solution; the mixed solution was stirred and mixed at 8000 r / min for 5 min; it was poured into a mold and placed in a refrigerator for freezing molding, and then freeze-dried to obtain a bio-based foam; the bio-based foam was immersed in an ethanol solution of methyltrimethoxysilane for 3 min for hydrophobic modification, and the bio-based foam adsorption material was obtained after drying.

[0061] Comparative Example 1:

[0062] 1.5 g of carrageenan powder and 1.5 g of vermiculite powder were weighed and dissolved in 100 g of deionized water, and stirred at 3000 r / min for at least 2 h at 60 ° C to completely dissolve them to obtain a first mixed solution; then 0.5 g of ferric chloride was added to the first mixed solution at 60 ° C and stirred at 3000 r / min for 5 min to obtain a second mixed solution; the second mixed solution was poured into a mold and placed in a refrigerator for freezing and forming, and then freeze-dried to obtain a bio-based foam; the bio-based foam was immersed in an ethanol solution of polydimethylsiloxane for 3 min for hydrophobic modification, and the bio-based foam adsorption material was obtained after drying.

[0063] Comparative Example 2:

[0064] 1.5 g of carrageenan powder and 0.25 g of silica fiber were weighed and dissolved in 100 g of deionized water, and stirred at 3000 r / min for at least 2 h at 60 ° C to completely dissolve them to obtain a first mixed solution; then 0.5 g of ferric chloride was added to the first mixed solution at 60 ° C and stirred at 3000 r / min for 5 min to obtain a second mixed solution; the second mixed solution was poured into a mold and placed in a refrigerator for freezing and forming, and then freeze-dried to obtain a bio-based foam; the bio-based foam was immersed in an ethanol solution of polydimethylsiloxane for 3 min for hydrophobic modification, and the bio-based foam adsorption material was obtained after drying.

[0065] Comparative Example 3:

[0066] 2.0 g of cellulose nanofiber powder and 1.5 g of halloysite powder were weighed and dissolved in 100 g of deionized water, and stirred at 50°C and 5000 r / min for at least 2 h to completely dissolve them to obtain a first mixed solution; then 0.5 g of polyamide-epichlorohydrin was added to the first mixed solution at 20°C and stirred at 3000 r / min for 5 min to obtain a second mixed solution; the second mixed solution was poured into a mold and placed in a refrigerator for freezing molding, and then freeze-dried to obtain a bio-based foam; the bio-based foam was immersed in an ethanol solution of methyltrimethoxysilane for 3 min for hydrophobic modification, and the bio-based foam adsorption material was obtained after drying.

[0067] Comparative Example 4:

[0068] 2.0 g of cellulose nanofiber powder and 0.25 g of glass fiber were weighed and dissolved in 100 g of deionized water, and stirred at 50°C and 5000 r / min for at least 2 h to completely dissolve them to obtain a first mixed solution; then 0.5 g of polyamide-epichlorohydrin was added to the first mixed solution at 20°C and stirred at 3000 r / min for 5 min to obtain a second mixed solution; the second mixed solution was poured into a mold and placed in a refrigerator for freezing molding, and then freeze-dried to obtain a bio-based foam; the bio-based foam was immersed in an ethanol solution of methyltrimethoxysilane for 3 min for hydrophobic modification, and the bio-based foam adsorption material was obtained after drying.

[0069] The performance test results of the products obtained in the above embodiments and comparative examples are as follows: Table 1 Adsorption capacity, contact angle and compressive strength results of bio-based foam adsorbent materials

[0070] The performance test results of each sample in Table 1 show that when 1.5g carrageenan is added as the bio-based polymer raw material, 1.5g vermiculite is used as the adsorbent, and 0.25g silica fiber is used as the reinforcing filler (Example 1), compared with the bio-based adsorption foam prepared by removing the reinforcing filler (Comparative Example 1), the adsorption capacity and contact angle are almost unchanged, but the compressive strength of the foam material is significantly reduced. This proves that the reinforcing filler will affect the compressive strength of the foam material. Figure 3 and Figure 4 The scanning electron microscopy results show that the lack of reinforcing fillers will make the pore structure of the foam material less strong, affecting the mechanical properties. The performance comparison between Example 3 and Comparative Example 3 also proves that reinforcing fillers will affect the mechanical properties of foam materials.

[0071] Comparing Example 2 and Comparative Example 2 as well as Example 4 and Comparative Example 4, removing the adsorbent filler from the material will reduce the porosity of the foam material and significantly reduce the oil absorption capacity.

[0072] By comparing Example 5 with Comparative Example 5, it can be seen that during the stirring process of the foam material, increasing the stirring speed will result in more pore structures being formed, which will increase the adsorption capacity to a certain extent. In addition, the process of adding a crosslinking agent is removed in Comparative Example 6, which reduces the compressive strength of the material.

[0073] The adsorption cycle changes of the samples of Example 3 and Comparative Example 3 for different organic pollutants are as follows: Figure 5 and Figure 6 As shown. Example 3 has better mechanical properties, higher compressive strength, stronger skeleton, better adsorption effect on organic pollutants, and better stability during oil absorption. Taking petroleum ether as an organic pollutant, the removal efficiency and adsorption capacity of Example 3 and Comparative Example 3 were tested as a function of the number of adsorption cycles. Figure 7 and Figure 8 It can be seen that with the increase of cycle times and the extension of usage time, the adsorption stability of the adsorption removal effect of Comparative Example 3 is poor and the adsorption capacity decays faster.

[0074] Fig. 9 This is the degradation performance test result of Example 2. The degradation rate of the bio-based foam adsorbent material increases with time, reaching more than 88% (average value of 5 times) after 30 days. Compared with the degradation conditions reported in the literature and patents, this is simpler and has a higher degradation rate.

Claims

1. A bio-based foam adsorption material, characterized in that It is obtained by processing the following raw materials in parts by weight: 0.1~10 parts of bio-based polymer, 0.01~5 parts of adsorbent, 0.1~10 parts of cross-linking agent, 0.01~5 parts of reinforcing agent, 0.01~5 parts of hydrophobic modifier; The bio-based polymer is a combination of one or more of carrageenan, sodium alginate, carboxymethyl cellulose, gelatin, cellulose nanofibers, konjac glucomannan, hydroxyethyl cellulose, chitosan, gum arabic, gellan gum, and starch; The adsorbent is a combination of one or more of vermiculite, sepiolite, montmorillonite, layered double hydroxide, zeolite, metal-organic framework material, and halloysite nanotubes; The hydrophobic modifier is any one or more combinations of methyltrimethoxysilane, hexadecyltriethoxysilane, 1H,1H,2H,2H-perfluorodecyltrichlorosilane, and polydimethylsiloxane.

2. The bio-based foam adsorption material according to claim 1, characterized in that: The cross-linking agent is a combination of one or more of glutaraldehyde, formaldehyde, genipin, polyvinyl alcohol, ferric chloride, aluminum chloride, and polyamide-epichlorohydrin.

3. The bio-based foam adsorption material according to claim 1, characterized in that: The reinforcing agent is a combination of one or more of glass fiber, silica fiber, attapulgite, mullite fiber, zirconium dioxide fiber and carbon fiber.

4. The method for preparing the bio-based foam adsorbent material according to any one of claims 1 to 3, characterized in that The steps include: The bio-based polymer, the adsorbent, the enhancer and water are stirred and mixed at 500-5000 r / min for 30 s-10 h at 0-90° C. to obtain a first mixed solution; the cross-linking agent is added to the first mixed solution at 100-10000 r / min for 30 s-30 min at 0-90° C. to obtain a second mixed solution; the second mixed solution is poured into a mold for molding and drying to obtain a bio-based foam; The bio-based foam can be hydrophobically modified by adding a hydrophobic modifier to obtain a bio-based foam adsorption material.

5. The preparation method according to claim 4, characterized in that: In the first mixed solution, the mass fraction of the bio-based polymer in water is 0.1% to 10%; the mass fraction of the adsorbent in water is 0.01% to 5%; and the mass fraction of the enhancer in water is 0.01% to 5%.

6. The preparation method according to claim 4, characterized in that: In the second mixed solution, the mass fraction of the cross-linking agent is 0.1% to 10%.

7. The preparation method according to claim 4, characterized in that: The hydrophobic modification method comprises soaking the bio-based foam in a hydrophobic modifier solution, vapor-phase evaporation deposition of the hydrophobic modifier, and spraying of the hydrophobic modifier, or one or more combinations thereof.

8. Use of the bio-based foam adsorption material according to any one of claims 1 to 3 in the adsorption and separation of organic pollutants in water.

9. The use according to claim 8, characterized in that: The organic pollutants include one or more of oils and organic dyes.

Citation Information

Patent Citations

  • Polyurethane oil-absorbing foam based on acetylated lignin modification as well as preparation method and application of polyurethane oil-absorbing foam

    CN114957969A

  • Biology base polymer aerogel oil absorption material and preparation method thereof

    CN105924686A

  • Silicon dioxide / cellulose magnetic foam and preparation method thereof

    CN106475067A

  • Hyperbranched hemicellulose polymer as well as preparation method and application thereof

    CN109456422A

  • Preparation method of oriented nanocellulose montmorillonite aerogel

    CN114479197A

Cited By

  • Foamed ceramic-based biofilm carrier as well as preparation method and application thereof

    CN120288947A

  • A foamed ceramic-based biofilm carrier and a preparation method and application thereof

    CN120288947B

  • Aerogel for treating emulsified oily wastewater and preparation method thereof

    CN120532465A

  • Preparation method for synthesizing water-absorbent resin based on acidic zeolite molecular sieve

    CN120737422A

  • Treatment method of HNIW wastewater

    CN120987501A